The challenges of neonatal sepsis management - Renato Soibelmann Procianoy; Rita C. Silveira (Elsevier, 2020)
Objectives: To present current evidence on the etiology, risk factors, diagnosis, and management of early and late neonatal sepsis. Source of data: Non-systematic review of the Medline (PubMed), Scopus, Web of Science, Cochrane, and Google Scholar databases regarding the following terms: neonatal sepsis, early neonatal sepsis, late neonatal sepsis, empirical antibiotic therapy, sepsis calculator, vancomycin, newborn, preterm newborn. Data synthesis: Neonatal sepsis is a frequent cause of neonatal morbidity and mortality. Its diagnosis is difficult. Continuous observation of the patient is critical to diagnostic suspicion. When neonatal sepsis is suspected, bacteriological tests should be collected. Vancomycin should not be routinely using in the empirical antibiotic regimen in late neonatal sepsis, and the main protective mechanisms against neonatal sepsis are handwashing and the use of breast milk. Conclusions: Newborns constitute a group that is more vulnerable to sepsis. Knowledge of risk factors and etiological agents allows a better approach to the newborn with sepsis. Resumo: Objetivos: Apresentar evidências atuais na etiologia, fatores de risco, diagnóstico e manejo da sepse neonatal precoce e tardia. Fontes de dados: Revisão não sistemática feita nas bases de dados Medline (PubMed), Scopus, Web of Science, Cochrane, Google Scholar sobre os temas sepse neonatal, sepse neonatal precoce, sepse neonatal tardia, antibioticoterapia empírica, sepsis calculator, vancomicina, recém-nascido, recém-nascido pré-termo. Síntese de dados: A sepse neonatal é uma causa frequente de morbimortalidade neonatal. O seu diagnóstico é difícil. A observação contínua do paciente é fundamental para uma suspeição diagnóstica. Ao se suspeitar de sepse neonatal devem-se coletar exames bacteriológicos. Não usar, rotineiramente, vancomicina no esquema empírico de antibiótico na sepse neonatal tardia. Os principais mecanismos protetores da sepse neonatal são a lavagem de mãos e o uso do leite materno. Conclusões: Os recém-nascidos constituem um grupo mais vulnerável à sepse. O conhecimento dos fatores de risco e dos agentes etiológicos permite uma melhor abordagem do recém-nascido séptico. Keywords: Neonatal sepsis, Sepsis calculator, Vancomycin, Coagulase-negative Staphylococcus, Group B Streptococcus, Palavras-chave: Sepse neonatal, Sepsis calculator, Vancomicina, Estafilococo coagulase negativo, Estreptococo grupo B